Bioavailability of the Common Cold Medicines in Jellies for Oral Administration - Ki Hyun Kim; Minju Jun; Mi-Kyung Lee (MDPI AG, 2020)
Jellies for oral administration have been suggested as alternative dosage forms to conventional tablets for improved palatability and compliances for pediatric and geriatric patients. To evaluate the effect of jelly formulation on the bioavailability of cold medicines, two types of jellies were prepared for a fixed-dose combination of acetaminophen (AAP), chlorpheniramine maleate (CPM), dextromethorphan hydrobromide (DMH), and dl-methylephedrine hydrochloride (MEH). Jelly-S and Jelly-H were fabricated using carrageenan and locust bean gum in the absence and presence of xanthan gum, respectively. In vitro dissolution and in vivo absorption of the four drugs in the jellies were compared with other conventional formulations, a syrup and two types of immediate-release (IR) tablets with different hardness, Tablet-S (15 kPa) and Tablet-H (20 kPa). All the formulations exhibited more than 80% dissolution rate within 2 h even though the syrup, Jelly-S, and Tablet-S showed higher 30-min dissolution compared to Jelly-H and Tablet-H. The dissolution rates from the jellies decreased with increasing pH, which resulted in the slowest dissolution in pH 6.8 compared to the syrup and IR tablets. When administered orally to beagle dogs, all five formulations were determined not to be bioequivalent. However, Jelly-S and Jelly-H showed 0.82-1.05 of the geometric mean ratios (GMRs) of AUC0-t for all four drugs compared to the syrup suggesting comparable absorption. In two IR tablets, GMRs of AUC0-t were in a range of 0.55-0.95 indicating a tendency of lower absorption than the syrup and jellies. In conclusion, jelly can be a patient-centered formulation with comparable bioavailability to syrup.